Bayesian network, a new method for modeling uncertainty in construction project management - Kiazad Abbasnezhad; Ramin Ansari (مهندسی و مدیریت ساخت, 2020)
As construction projects consist of different stake holders and operate in a dynamic environment encounter with many risks. Uncertainties affect all project management aspects. Because of that risk modeling in project management has been a big challenge for researchers. Classic methods of uncertainty modeling in project management (fuzzy, objective probability…,etc.) need a lot recorded data for modeling and inference. These data are not accessible every time. Bayesian novel method by participating several data source has made a flexible framework for modeling risks. Project management according to project management body of knowledge (PMBOK) has distributed to deterministic knowledge areas. In this paper application of Bayesian network approach for modeling uncertainty in project management knowledge areas has been reviewed and recent researches has been sorted. The way of future researches almost has been cleared. a b c d f e g h i j k o m n o p q r s t